Multi-component plasma fluid approach to sparking enhanced burns as a complication of diathermy - Radmilovic-Radjenovic, Marija; Radjenovic, Branislav (International Surgery Journal, 2020)
Background: The effects of electric currents flowing through a human body vary from no perceptible to severe tissue injury caused by the electrosurgical spark. Although modern electrodes have been designed to minimize this complication, it was reported that burns have accounted for 70% of the injuries during electro surgery. Some risks of complications depend on a surgeon's knowledge of instruments and safety aspects of technical equipment. The use of alcohol and spirit-based skin preparation solutions brings another risk of burn injuries. Methods: Apart from the experimental methods, computer modelling is shown to be an effective approach to improve the performance of electrosurgical procedure. The benefits of simulation assisted electro surgery include no ethical approval, low cost, safe and the most important removing conditions that may lead to tissue burns. Here, the onset of sparking between the electrosurgical electrodes has been studied by using the multi-component plasma fluid model. Results: It was found that the electrode shape significantly affects the sparking formation. The minimum voltage required for sparking has been achieved for cylinder-cylinder configuration, while for other arrangements breakdown voltages are higher. Electrical sparks do not occur equally in both directions between active and passive electrodes due to electrical asymmetries. Conclusions: This study is dealing with application of multi-component plasma fluid model in simulating sparks produced between electrosurgical electrodes of various shapes, materials and dimensions. Our simulation model offers substantially greater physical fidelity as compared to simulators that use simple geometry. The obtained results are applicable for prevention of potential complications during diathermy procedure.